A lithium ion battery positive electrode material and preparation method thereof and a lithium ion battery
By adopting the lithium-ion battery positive electrode material with the chemical formula of LiAO2·xLi2BO2 or LiAO2@xLi2BO2, the problem of additional pre-embedded lithium in the prior art is solved, and the high discharge capacity of the battery and the effect of reducing production costs is achieved.
Patent Information
- Application Number
- CN202210007277.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-05
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-01-05
AI Technical Summary
Existing lithium-ion batteries require additional pre-embedded lithium during the synthesis process, resulting in increased production costs and difficulties, and are not conducive to mass production.
A lithium-ion battery positive electrode material is used, with the chemical formula of LiAO2·xLi2BO2 or LiAO2@xLi2BO2, which is prepared by high-temperature sintering and solid-phase reaction. It has its own prelithiation effect, so that the negative electrode can be directly prelithiated.
The positive electrode material can directly provide lithium ions for the formation of the negative electrode SEI film during the battery shaping stage, avoid consuming lithium ions in the positive electrode material, increase the discharge capacity of the battery, and reduce the residual lithium of the system.
Smart Images

Figure CN114530591B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] With the rapid development of the new energy industry, lithium-ion batteries have attracted much attention as good energy storage devices. Among them, ternary positive electrode materials have been widely used in power batteries due to their high capacity, good cycle stability and safety, and have become the focus of research in recent years.
[0003] The formation of the negative electrode SEI film during the formation of lithium-ion batteries consumes lithium ions, and these lithium ions come from the positive electrode material, which leads to a decrease in the coulombic efficiency and discharge capacity of the battery. Therefore, many battery manufacturers need to pre-embed lithium in the negative electrode during the battery formation stage during the battery manufacturing process to reduce the loss of lithium ions in the positive electrode material, but this method of pre-embedding lithium greatly increases the cost and difficulty of battery production, which is not conducive to mass production of batteries. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a positive electrode material for a lithium-ion battery and a preparation method thereof and a lithium-ion battery, wherein the positive electrode material for a lithium-ion battery can directly pre-lithiate the negative electrode without adding additional steps, which is conducive to the mass production of batteries.
[0005] The above technical objectives of the present invention are achieved through the following technical solutions:
[0006] A positive electrode material for a lithium-ion battery, wherein the chemical formula of the positive electrode material for the lithium-ion battery is LiAO2·xLi2BO2 or LiAO2@xLi2BO2; in the chemical formula, A includes at least one of Ni and Co, and B is at least one of Ni, Co, Mn, Cu and Zn, wherein 0<x≤0.05.
[0007] Preferably, the A also includes at least one of Mn or Al.
[0008] Preferably, the average valence state of A in the LiAO2·xLi2BO2 or LiAO2@xLi2BO2 is +3, and the average valence state of B is +2.
[0009] Preferably, the LiAO2 in the LiAO2·xLi2BO2 or LiAO2@xLi2BO2 has a hexagonal crystal structure.
[0010] Preferably, the Li2BO2 in the LiAO2·xLi2BO2 or LiAO2@xLi2BO2 has an orthorhombic crystal structure.
[0011] Preferably, the LiAO2 is at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and lithium nickel cobalt manganese aluminum oxide.
[0012] Preferably, the particle size D50 of the lithium-ion battery positive electrode material is 1-13 μm.
[0013] Preferably, when the chemical formula of the positive electrode material is LiAO2·xLi2BO2, Li2BO2 particles are uniformly distributed in the LiAO2 particles; when the chemical formula of the positive electrode material is LiAO2@xLi2BO2, Li2BO2 is coated on the surface of the LiAO2 particles.
[0014] A method for preparing the positive electrode material of a lithium ion battery as described above comprises the following steps:
[0015] The precursor containing A and the lithium source are sintered at high temperature to obtain LiAO2, and then LiAO2 and the oxide of B are subjected to a high temperature solid phase reaction under an inert atmosphere, or LiAO2 and the oxide of B are subjected to a high temperature and high pressure solvent thermal reaction to obtain the lithium ion battery positive electrode material LiAO2@xLi2BO2;
[0016] or
[0017] The precursor containing A and the lithium source are sintered at high temperature to obtain LiAO2, the precursor containing B and the lithium source are sintered at high temperature to obtain Li2BO2, and then LiAO2 and Li2BO2 are mixed to obtain the lithium ion battery positive electrode material LiAO2·xLi2BO2.
[0018] Preferably, the reaction temperature in the high temperature solid phase reaction is 400-800° C., and the reaction time is 4-12 h.
[0019] Preferably, the LiAO2 and the Li2BO2 are mixed by ball milling or high-temperature solvent thermal mixing.
[0020] Preferably, the inert atmosphere is at least one of nitrogen, argon and helium.
[0021] A lithium ion battery comprises the lithium ion battery positive electrode material as described above.
[0022] The beneficial effects of the present invention are:
[0023] (1) The lithium-ion battery positive electrode material of the present invention has a pre-lithiation effect. The Li2BO2 contained therein can directly pre-lithiate the negative electrode during the lithium-ion battery formation stage, and can provide additional lithium ions for the formation of the negative electrode SEI film, thereby avoiding the consumption of lithium ions in the main body of the positive electrode material and improving the discharge capacity of the battery;
[0024] (2) In the preparation method of the positive electrode material for lithium-ion batteries of the present invention, residual lithium in the positive electrode material substrate and B oxide are used to form an orthorhombic structure material Li2BO2, thereby reducing the residual lithium in the system;
[0025] (3) The lithium-ion battery positive electrode material of the present invention will not have a negative impact on the cycle and rate performance of the battery, and the pre-lithiation of the negative electrode can be achieved without adding additional steps during the battery formation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 XRD diagrams of the positive electrode materials of lithium ion batteries of Example 1 and Comparative Example 1;
[0027] Figure 2 The SEM images of the lithium-ion battery positive electrode materials of Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with specific embodiments.
[0029] Embodiment 1:
[0030] A lithium-ion battery positive electrode material, its chemical formula is: LiNi 0.8 Co 0.1 Mn 0.1 O2@0.02Li2CuO2, particle size D50 is 6.0μm, LiNi 0.8 Co 0.1 Mn 0.1 LiNi in O2@0.02Li2CuO2 0.8 Co 0.1 Mn 0.1 O2 has a hexagonal structure, LiNi 0.8 Co 0.1 Mn 0.1 The Li2CuO2 in O2@0.02Li2CuO2 has an orthorhombic crystal structure.
[0031] The method for preparing the above-mentioned lithium ion battery positive electrode material comprises the following steps:
[0032] (1) Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and lithium salt LiOH·H2O were mixed at a molar ratio of Li / Me=1.02, and then the mixture was heated to 800°C in an oxygen atmosphere for 10 hours, and LiNi was obtained by crushing and sieving. 0.8 Co 0.1 Mn 0.1 O2;
[0033] (2) LiNi prepared in step (1) 0.8 Co 0.1 Mn 0.1 O2 and CuO were mixed in a molar ratio of (Ni+Co+Mn):Cu=1:0.02, and then the mixture was heated to 500°C in a nitrogen atmosphere for 6 hours to obtain the positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2@0.02Li2CuO2.
[0034] A lithium ion battery, the preparation method of which comprises the following steps:
[0035] (1) The positive electrode material of this embodiment is used as the positive electrode active material, mixed with conductive carbon black (SP) and polyvinylidene fluoride (PVDF) in a weight ratio of 0.9:0.05:0.05, added with solvent nitrogen-methylpyrrolidone (NMP) for stirring, and then coated on aluminum foil after homogenization, and dried to obtain a positive electrode sheet;
[0036] (2) The positive electrode sheet is used as the positive electrode of the lithium-ion battery, and the negative electrode sheet with graphite as the negative electrode active material is used as the negative electrode to assemble a lithium-ion button-type full battery.
[0037] Embodiment 2:
[0038] A lithium-ion battery positive electrode material, its chemical formula is: LiNi 0.5 Co 0.2 Mn 0.3 O2@0.05Li2Cu 0.5 Ni 0.5 O2, particle size D50 is 7μm, LiNi 0.5 Co 0.2 Mn 0.3 O2@0.05Li2Cu 0.5 Ni 0.5 LiNi in O2 0.5 Co 0.2 Mn 0.3 O2 has a hexagonal structure, LiNi 0.5 Co 0.2 Mn 0.3 O2@0.05Li2Cu 0.5 Ni 0.5 Li2Cu in O2 0.5 Ni 0.5 O2 has an orthorhombic crystal structure.
[0039] The method for preparing the above-mentioned lithium ion battery positive electrode material comprises the following steps:
[0040] (1) Ni 0.5 Co0.2 Mn 0.3 (OH)2 and lithium salt Li2CO3 were mixed in a molar ratio of Li / Me = 1.05, and then the mixture was heated to 900 ° C in an oxygen atmosphere for 12 hours, and LiNi was obtained by crushing and sieving. 0.5 Co 0.2 Mn 0.3 O2;
[0041] (2) LiNi prepared in step (1) 0.5 Co 0.2 Mn 0.3 O2 was mixed with CuO and NiO in a molar ratio of (Ni+Co+Mn):Cu:Ni=1:0.025:0.025, and then the mixture was heated to 550℃ in a nitrogen atmosphere for 6h to obtain the positive electrode material LiNi 0.5 Co 0.2 Mn 0.3 O2@0.05Li2Cu 0.5 Ni 0.5 O2.
[0042] A lithium ion battery, the preparation method of which comprises the following steps:
[0043] (1) The positive electrode material of this embodiment is used as the positive electrode active material, mixed with SP and PVDF in a weight ratio of 0.8:0.1:0.1, added with solvent NMP for stirring, and then coated on aluminum foil after homogenization, and dried to obtain a positive electrode sheet;
[0044] (2) The positive electrode sheet is used as the positive electrode of the lithium-ion battery, and the negative electrode sheet with graphite as the negative electrode active material is used as the negative electrode to assemble a lithium-ion button-type full battery.
[0045] Embodiment 3:
[0046] A lithium-ion battery positive electrode material, its chemical formula is: LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2·0.05Li2CuO2, particle size D50 is 13μm, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 LiNi in O2·0.05Li2CuO2 1 / 3 Co 1 / 3 Mn 1 / 3 O2 has a hexagonal structure, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Li2CuO2 in O2·0.05Li2CuO2 has an orthorhombic crystal structure.
[0047] The method for preparing the above-mentioned lithium ion battery positive electrode material comprises the following steps:
[0048] (1) Ni 1 / 3 Co 1 / 3 Mn 1 / 3 (OH)2 and lithium salt Li2CO3 were mixed in a molar ratio of Li / Me = 1.08, and then the mixture was heated to 950 ° C in an oxygen atmosphere for 14 hours, and LiNi was obtained by crushing and sieving. 1 / 3 Co 1 / 3 Mn 1 / 3 O2;
[0049] (2) CuO and LiOH·H2O are mixed in a molar ratio of Li / Cu=2:1, and the mixture is heated to 500°C under a nitrogen atmosphere for 4 hours, and Li2CuO2 is obtained by crushing and sieving;
[0050] (3) LiNi prepared in step (1) 1 / 3 Co 1 / 3 Mn 1 / 3 O2 is mixed with the Li2CuO2 prepared in step (2) in a molar ratio of (Ni+Co+Mn):Cu=1:0.05 to obtain the positive electrode material LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2·0.05Li2CuO2.
[0051] A lithium ion battery, the preparation method of which comprises the following steps:
[0052] (1) The positive electrode material of this embodiment is used as the positive electrode active material, mixed with SP and PVDF in a weight ratio of 0.8:0.15:0.05, added with solvent NMP for stirring, and coated on aluminum foil after homogenization, and dried to obtain a positive electrode sheet;
[0053] (2) The positive electrode sheet is used as the positive electrode of the lithium-ion battery, and the negative electrode sheet with graphite as the negative electrode active material is used as the negative electrode to assemble a lithium-ion button-type full battery.
[0054] Embodiment 4:
[0055] A lithium-ion battery positive electrode material, its chemical formula is: LiNi 0.8 Co 0.1 Mn 0.1 O2@0.05Li2CuO2, particle size D50 is 10μm, LiNi 0.8 Co 0.1 Mn 0.1 LiNi in O2@0.02Li2CuO2 0.8 Co 0.1 Mn0.1 O2 has a hexagonal structure, LiNi 0.8 Co 0.1 Mn 0.1 The Li2CuO2 in O2@0.02Li2CuO2 has an orthorhombic crystal structure.
[0056] The method for preparing the above-mentioned lithium ion battery positive electrode material comprises the following steps:
[0057] (1) Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and lithium salt LiOH·H2O were mixed in a molar ratio of Li / Me=1.04, and then the mixture was heated to 750°C in an oxygen atmosphere for 12 hours, and LiNi was obtained by crushing and sieving. 0.8 Co 0.1 Mn 0.1 O2;
[0058] (2) LiNi prepared in step (1) 0.8 Co 0.1 Mn 0.1 O2 and CuO were added to anhydrous ethanol solvent in a molar ratio of (Ni+Co+Mn):Cu=1:0.05, and then transferred to a high-pressure reactor for solvothermal reaction. The reaction conditions were 200℃ for 6h, and the positive electrode material LiNi was obtained after filtration and drying. 0.8 Co 0.1 Mn 0.1 O2@0.02Li2CuO2.
[0059] A lithium ion battery, the preparation method of which comprises the following steps:
[0060] (1) The positive electrode material of this embodiment is used as the positive electrode active material, mixed with conductive carbon black (SP) and polyvinylidene fluoride (PVDF) in a weight ratio of 0.8:0.1:0.1, added with solvent nitrogen-methylpyrrolidone (NMP) for stirring, and then coated on aluminum foil after homogenization, and dried to obtain a positive electrode sheet;
[0061] (2) The positive electrode sheet is used as the positive electrode of the lithium-ion battery, and the negative electrode sheet with graphite as the negative electrode active material is used as the negative electrode to assemble a lithium-ion button-type full battery.
[0062] Embodiment 5:
[0063] A lithium-ion battery positive electrode material, its chemical formula is: LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Zn 0.5O2, particle size D50 is 10μm, LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Zn 0.5 LiNi in O2 0.8 Co 0.15 Al 0.05 O2 has a hexagonal structure, LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Zn 0.5 Li2Cu in O2 0.5 Zn 0.5 O2 has an orthorhombic crystal structure.
[0064] The method for preparing the above-mentioned lithium ion battery positive electrode material comprises the following steps:
[0065] (1) Ni 0.8 Co 0.15 Al 0.05 (OH)2 and lithium salt LiOH·H2O were mixed at a molar ratio of Li / Me=1.02, and then the mixture was heated to 800°C in an oxygen atmosphere for 10 hours, and LiNi was obtained by crushing and sieving. 0.8 Co 0.15 Al 0.05 O2;
[0066] (2) LiNi prepared in step (1) 0.8 Co 0.15 Al 0.05 O2 was mixed with CuO and ZnO in a molar ratio of (Ni+Co+Mn):Cu:Zn=1:0.01:0.01, and then the mixture was heated to 450°C in a nitrogen atmosphere for 8 hours to obtain the positive electrode material LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Zn 0.5 O2.
[0067] A lithium ion battery, the preparation method of which comprises the following steps:
[0068] (1) The positive electrode material of this embodiment is used as the positive electrode active material, mixed with conductive carbon black (SP) and polyvinylidene fluoride (PVDF) in a weight ratio of 0.8:0.1:0.1, added with solvent nitrogen-methylpyrrolidone (NMP) for stirring, and then coated on aluminum foil after homogenization, and dried to obtain a positive electrode sheet;
[0069] (2) The positive electrode sheet is used as the positive electrode of the lithium-ion battery, and the negative electrode sheet with graphite as the negative electrode active material is used as the negative electrode to assemble a lithium-ion button-type full battery.
[0070] Embodiment 6:
[0071] A lithium-ion battery positive electrode material, its chemical formula is: LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Mn 0.5 O2, particle size D50 is 10μm, LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Mn 0.5 LiNi in O2 0.8 Co 0.15 Al 0.05 O2 has a hexagonal structure, LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Mn 0.5 Li2Cu in O2 0.5 Mn 0.5 O2 has an orthorhombic crystal structure.
[0072] The above method for preparing the positive electrode material for a lithium-ion battery is different from that of Example 5 only in that ZnO in step (2) of Example 5 is replaced by MnO.
[0073] Embodiment 7:
[0074] A lithium-ion battery positive electrode material, its chemical formula is: LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Co 0.5 O2, particle size D50 is 10μm, LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Co 0.5 LiNi in O2 0.8 Co 0.15 Al 0.05 O2 has a hexagonal structure, LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Co 0.5Li2Cu in O2 0.5 Co 0.5 O2 has an orthorhombic crystal structure.
[0075] The above method for preparing the positive electrode material for a lithium-ion battery is different from that of Example 5 only in that ZnO in step (2) of Example 5 is replaced by Co(OH)2.
[0076] Embodiment 8:
[0077] A lithium-ion battery positive electrode material, its chemical formula is: LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Fe 0.5 O2, particle size D50 is 10μm, LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Fe 0.5 LiNi in O2 0.8 Co 0.15 Al 0.05 O2 has a hexagonal structure, LiNi 0.8 Co 0.15 Al 0.05 O2@0.02Li2Cu 0.5 Fe 0.5 Li2Cu in O2 0.5 Fe 0.5 O2 is an orthorhombic crystal structure. Compared with Example 5, the difference is:
[0078] The above method for preparing the positive electrode material for a lithium-ion battery is different from that of Example 5 only in that ZnO in step (2) of Example 5 is replaced by Fe(OH)2.
[0079] Comparative Example 1:
[0080] A lithium-ion battery positive electrode material, its chemical formula is: LiNi 0.8 Co 0.1 Mn 0.1 O2, particle size D50 is 6.0μm.
[0081] The method for preparing the above-mentioned lithium ion battery positive electrode material comprises the following steps:
[0082] The precursor Ni 0.8 Co 0.1 Mn 0.1(OH)2 and lithium salt LiOH·H2O were mixed at a molar ratio of Li / Me=1.02, and then the mixture was heated to 800°C in an oxygen atmosphere for 10 hours, and LiNi was obtained by crushing and sieving. 0.8 Co 0.1 Mn 0.1 O2.
[0083] A lithium ion battery, the preparation method of which comprises the following steps:
[0084] (1) The positive electrode material of this comparative example is used as the positive electrode active material, mixed with SP and PVDF in a weight ratio of 0.9:0.05:0.05, added with solvent NMP for stirring, and coated on aluminum foil after homogenization, and dried to obtain a positive electrode sheet;
[0085] (2) The positive electrode sheet is used as the positive electrode of the lithium-ion battery, and the negative electrode sheet with graphite as the negative electrode active material is used as the negative electrode to assemble a lithium-ion button-type full battery.
[0086] Comparative Example 2:
[0087] A lithium-ion battery positive electrode material, its chemical formula is: LiNi 0.8 Co 0.1 Mn 0.1 O2, particle size D50 is 6.0μm.
[0088] The method for preparing the above-mentioned lithium ion battery positive electrode material comprises the following steps:
[0089] (1) Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and lithium salt LiOH·H2O were mixed at a molar ratio of Li / Me=1.02, and the mixture was heated to 800°C in an oxygen atmosphere for 10 hours, and then crushed and sieved to obtain a sintered matrix;
[0090] (2) The monoalkyl matrix obtained in step (1) was washed with water, filtered and dried, and then heated to 500° C. in a nitrogen atmosphere for 6 h to obtain a positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0091] A lithium ion battery, the preparation method of which comprises the following steps:
[0092] (1) The positive electrode material of this comparative example is used as the positive electrode active material, mixed with SP and PVDF in a weight ratio of 0.9:0.05:0.05, added with solvent NMP for stirring, and coated on aluminum foil after homogenization, and dried to obtain a positive electrode sheet;
[0093] (2) The positive electrode sheet is used as the positive electrode of the lithium-ion battery, and the negative electrode sheet with graphite as the negative electrode active material is used as the negative electrode to assemble a lithium-ion button-type full battery.
[0094] Test example
[0095] The residual lithium test was performed on the positive electrode materials of the lithium ion batteries of Examples 1-3 and Comparative Examples 1-2, respectively, and the first discharge capacity and the first coulomb efficiency (first efficiency) of the lithium ion batteries of Examples 1-3 and Comparative Examples 1-2 were tested, respectively. The test results are shown in Table 1.
[0096] Table 1: Lithium-ion battery cathode materials and lithium-ion battery performance test results
[0097]
[0098] At the same time, the lithium ion battery positive electrode materials of Example 1 and Comparative Example 1 were subjected to XRD test and SEM test, respectively. The results of the XRD test are as follows: Figure 1 The results of the SEM test are shown in Figure 2 shown.
[0099] As can be seen from Table 1, the residual lithium of the positive electrode material in Example 1 is significantly reduced compared with that in Comparative Example 1, indicating that the preparation method of the lithium-ion battery positive electrode material of the present invention has the effect of reducing the residual lithium of the material, and the effect of reducing the residual lithium is equivalent to the water washing method in Comparative Example 2.
[0100] At the same time, the lithium-ion battery positive electrode material of Example 1 has a significant improvement in the first coulombic efficiency and the first discharge capacity compared with the comparative example 1, indicating that the lithium-ion battery positive electrode material of the present invention has a pre-lithiation effect, can convert residual lithium into Li2BO2, and play a role in the formation process of the lithium-ion battery, replenishing the Li+ consumed in the formation of the negative electrode SEI film, thereby improving the first coulombic efficiency and capacity of the battery.
[0101] In addition, by Figure 1 It can be seen that the LiNi of Example 1 0.8 Co 0.1 Mn 0.1 O2 was sintered again after adding CuO to form Li2CuO2. Figure 2 It can be seen that the scanning electron microscope image of the lithium-ion battery positive electrode material of Example 1 shows that some larger single-crystalline primary particles are formed and evenly dispersed in the lithium-ion battery positive electrode material, indicating that Li2CuO2 is generated in the lithium-ion battery positive electrode material of Example 1.
[0102] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A positive electrode material for a lithium-ion battery, characterized in that: The chemical formula of the positive electrode material for a lithium ion battery is LiAO2@xLi2BO2; in the chemical formula, A includes at least one of Ni and Co, and B is at least one of Ni, Co, Mn, Cu and Zn, wherein 0<x≤0.05; LiAO2 in the LiAO2@xLi2BO2 is a hexagonal crystal structure; Li2BO2 in the LiAO2@xLi2BO2 is an orthorhombic crystal structure; the particle size D50 of the positive electrode material for a lithium ion battery is 1-13 μm; the preparation method of the positive electrode material for a lithium ion battery comprises the following steps: high-temperature sintering a precursor containing A and a lithium source to obtain LiAO2, and then subjecting LiAO2 to a high-temperature solid-phase reaction with an oxide of B under an inert atmosphere, or subjecting LiAO2 to a high-temperature and high-pressure solvent thermal reaction with an oxide of B to obtain the positive electrode material for a lithium ion battery LiAO2@xLi2BO2; when the chemical formula of the positive electrode material is LiAO2@xLi2BO2, Li2BO2 is coated on the surface of the LiAO2 particles.
2. A lithium ion battery positive electrode material according to claim 1, characterized in that: The A further includes at least one of Mn and Al.
3. A lithium-ion battery positive electrode material according to claim 1, characterized in that: The LiAO2 is at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and lithium nickel cobalt manganese aluminum oxide.
4. A lithium-ion battery positive electrode material according to claim 1, characterized in that: The reaction temperature in the high temperature solid phase reaction is 400-800° C. and the reaction time is 4-12 hours.
5. A lithium ion battery, characterized in that: The lithium-ion battery positive electrode material comprises any one of claims 1 to 3.
Citation Information
Patent Citations
Cathode material of lithium ion battery and preparation method and lithium ion battery
CN110993933A
Positive additive and preparation method and application thereof
CN111653770A
High-voltage lithium ion battery and preparation method thereof
CN112397766A
Lithium self-supplementing type single crystal nickel-cobalt-manganese composite ternary positive electrode material and preparation method thereof
CN112652748A
Positive pole piece of lithium ion battery, and preparation method and application thereof
CN113782706A